THE RELATIONSHIP AMONG LEARNING MOTIVATION, LEARNING FACILITIES, AND PEERS WITH STUDENTS MATHEMATICS LEARNING OUTCOME - Reni Anggreani; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2019)
Learning motivation is still low, learning facilities are still inadequate, and peers are still poor. The objectives in this research to understanding there or not the positive relationship and the signification between learning motivation, learning facilities, and peers with the result of the study of mathematics to students class VIII Junior High School (SMP) Muhammadiyah 1 Mlati of Sleman Regency even semester in the academic year 2017/2018. This research population is all of the students class VIII SMP Muhammadiyah 1 Mlati of Sleman Regency even semester in the academic year 2017/2018, which consists of five classes totaling 162 students. Class VIIIC, as a research sample class, was taken by random sampling technique for the class. Data collection techniques used a questionnaire method to obtain data on learning motivation, learning facilities, peers, and test methods to obtain data on mathematics learning outcomes. Research instrument test: validity test, different power test, and reliability test. Analysis prerequisite tests include normality test, linearity test, and independence test. Data analysis using product moment analysis and multiple linear regression analysis. The research results show a positive and significant relationship between learning motivation, learning facilities, and peers with mathematics to students class VIII SMP Muhammadiyah 1 Mlati of Sleman Regency even semester in 2017/2018. At the significant level 5%, 4,1174 and 2,99, with multiple correlation coefficients 0,5751 and determinant of coefficient double 0,3307 with multiple regression equations are three variables . Relative contribution , = dan = 13,4008% and effective contribution = = dan = .